2006
DOI: 10.1074/jbc.m510841200
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Amino Latch of Staphylococcal α-Hemolysin in Pore Formation

Abstract: Staphylococcal ␣-hemolysin (␣HL) is a ␤ barrel pore-forming toxin that is secreted by the bacterium as a water-soluble monomeric protein. Upon binding to susceptible cells, ␣HL assembles via an inactive prepore to form a water-filled homoheptameric transmembrane pore. The N terminus of ␣HL, which in the crystal structure of the fully assembled pore forms a latch between adjacent subunits, has been thought to play a vital role in the prepore to pore conversion. For example, the deletion of two N-terminal residu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 59 publications
3
26
0
Order By: Relevance
“…The N terminus of LukF is in a protease sensitive conformation, whereas the N terminus of LukS is protease-resistant. 2) In agreement with work on the ␣HL pore (see previous report (36)), the N termini of the LukF and LukS subunits are not required for pore formation. This was demonstrated in experiments where both LukF and LukS were truncated, as well as in experiments where a truncated subunit was assembled with its fulllength counterpart.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…The N terminus of LukF is in a protease sensitive conformation, whereas the N terminus of LukS is protease-resistant. 2) In agreement with work on the ␣HL pore (see previous report (36)), the N termini of the LukF and LukS subunits are not required for pore formation. This was demonstrated in experiments where both LukF and LukS were truncated, as well as in experiments where a truncated subunit was assembled with its fulllength counterpart.…”
Section: Discussionsupporting
confidence: 77%
“…8A, stage 4). However, in the preceding report (36), we demonstrated that in various mutants of ␣HL the formation of a protease-resistant latch from Freshly translated LukF-S9C, LukS-D3C, and ␣HL-S3C labeled with 35 S[cysteine] were allowed to bind to rRBC membranes. In the cases of the leukocidins, the unlabeled WT counterpart was included to ensure pore formation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This model for the linker assumes that the N terminus of one subunit latches tightly onto a second, as seen in the crystal structure of the WT heptamer. However, work in our laboratory has revealed that the N terminus of ␣HL is not critical for the formation of oligomers, and up to 17 residues can be deleted while retaining the ability to form pores (32). Furthermore, the related Vibrio cholerae cytolysin has no such N-terminal domain (33).…”
Section: Resultsmentioning
confidence: 99%